Comparison of Outcomes of Laparoscopic Versus Open Resection in Colorectal Carcinoma with Obstruction - Abbas Zafar, Hasaan Masood Hiraj, Haroon Ur Rashid, Irfan Nabi Khan, Aamer Wadud, Muhammad Farooq (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Colorectal carcinoma is among the leading malignancies worldwide, with obstruction being a common and serious presentation. Surgical resection remains the mainstay of treatment, traditionally performed through open surgery. With advances in minimally invasive techniques, laparoscopic resection has been increasingly utilized, though its role in obstructed cases remains debated. Objectives: To compare the outcomes of laparoscopic versus open resection in patients with colorectal carcinoma presenting with obstruction. Study Design & Setting: A comparative study was conducted at the Department of General Surgery, Sheikh Zayed Hospital Rahim Yar Khan from Jan 2023 to June 2023. Methodology: A total of 130 patients with obstructed colorectal carcinoma were included, with 65 undergoing laparoscopic resection and 65 undergoing open resection. Perioperative parameters, postoperative complications, and recovery outcomes were recorded. Data were analyzed using SPSS version 26, with t-test and chi-square test applied. A p-value ≤ 0.05 was considered significant. Results: The mean age was 56.0 ± 11.0 years, with a male predominance (56.9%). Duration of surgery was longer in the laparoscopic group (150.4 ± 25.2 vs. 135.6 ± 28.4 min, p = 0.004), but blood loss was significantly less (220.5 ± 80.6 vs. 310.3 ± 95.7 mL, p < 0.001). Wound infection was lower in laparoscopic cases (9.2% vs. 21.5%, p = 0.048). Return of bowel sounds, oral intake, and hospital stay were significantly earlier in laparoscopic patients (all p < 0.001). Mortality was low and comparable between groups. Conclusion: Laparoscopic resection provided better short-term recovery outcomes than open resection while maintaining comparable safety in obstructed colorectal carcinoma. Keywords: Anastomosis, Colorectal carcinoma, Laparoscopic resection, Obstruction, Open resection, Postoperative complications, Surgical outcomes